Increasing Safety Awareness Through the WISE Program for Indonesian MSMEs - Rizqi Novita Sari; Sinta Dewi; Mega Cattleya PA Islami; Gading Adian Kun Sa'idan; Jafni Fara Zahirah (Future Science, 2023)
Micro, Small and Medium Enterprises (MSMEs) experience difficulties in managing Occupational Safety and Health (OHS) in the workplace. Apart from poor OHS conditions, it is also caused by a lack of systematic OHS management. Work Improvement in Small Enterprises (WISE) is a participatory training program to help MSMEs increase workplace productivity and efficiency through implementing OHS aspects. The high number of accidents and injuries occurred 20% more often in small companies compared to companies with more than 100 workers and 40% more often than in companies with more than 1000 workers. So, it can be concluded that MSMEs are more vulnerable to work accidents and K3 management in MSMEs is still very lacking. This research aims to reduce the risk of work accidents in MSMEs using the WISE method.